Living toward the end. Issue 4 (10th September 2019) - Sponheim, Paul R.
Abstract: Human beings look to the end as terminus, a passing away when the individual's life story will be complete. Against a cultural tendency to deny death, Christians—claiming a Creator God who does not die—can accept their finitude in principle and aspire to a "high definition" ending. That hope is threatened by the devastating reality of dementia. But Kierkegaard reminds us that the "positive third" of selfhood is not to be identified with mentality and Whitehead stresses that the reception of the inrushing world does not depend on conscious mentality. Against the prevalent culture of individualism, a person of faith can recognize the constitutive role of community past and present. She can find in her terminus a telos, a passing on of life to the others as she steps aside. Is there more? The Newer Testament proclaims a new creation in which life's ending is transformed by the sense of end as beginning, end as advent. This omega as alpha entails both continuity and discontinuity. As to discontinuity, the Christian envisions a life "beyond Eden, " where the perilous gift of freedom is transformed in an integrating knowledge of self, world, and God—fulfilling the calling given to all as created in God's image. This sense of end does not function as an "escape to a transcendent elsewhere, " but motivates and empowers the believer to care for the suffering victims of this volatile and violent age.